Expatriation: the focus on psychological contract - Silva, Susana (2017)
In the past few years, the number of expatriates has shown a growth trend worldwide. Accordingly, the expatriate management, which integrates the subsystem of International Human Resources Management, has now a renewed attention and has been growing as an intervention area of Human Resources Management. Therefore, the psychological contract has been seen, more and more, as a relevant factor in explaining the labour relations and the number of studies around this theme has increased. The success of expatriation is directly influenced by the psychological contract and depends largely on how HRM practices are developed (Homem & Tolfo, 2008). Understanding the reaction of workers through changes (Bligh & Carsten, 2005; Shield et al., 2002) is essential, since the response behaviour can be a crucial contribution to the success or failure of the international assignment. In the same context, we are witnessing an increasing attention on the contribution that the Psychological Contract may have under uncertainty. The individual, as an employee of an organization that decides to accept an international assignment and move to another country, needs to fit in a continuous and motivating relationship with the employer. The concept of the psychological contract is fundamental to the understanding of labour relations, based on the perceptions of those involved. Many aspects of these relationships are implicit (unwritten) which can cause different interpretations of expectations, promises and obligations between parties. Several authors argue that the psychological contract is the key to understand and manage the attitudes and behaviour of individuals in organizations (Bunderson, 2001; Kraimer et al., 2005; Lemire & Rouillard, 2005). The goal of this work is to understand the psychological contract in expatriates: before the assignment, after adjustment to the host country and repatriation. A qualitative methodology was used, and for that we applied semi-structured individual interviews and sociographic questionnaire to people who were, at the time, expatriate. In total, ten interviews were conducted and the analysis of the interviews were made through Grounded Theory. The results suggest that there is only fulfilment of the psychological contract in the stage of the preparation of the international assignment, existing, on the other hand, breach of the psychological contract during expatriation and at repatriation, according to the perception that expatriates have about the end of expatriation. However, most of the interviewed expatriates evaluates positively the expatriation experience, although organizations appear to have just a few rules to support expatriate, particularly logistical and financial support, and not having a complete and thorough program of support to the expatriation management. The results also suggest that it is essential that organizations encourage communication with expatriates and promote the continuous support, which should be constant and intrinsic to all phases of expatriation in order to avoid the “abandon” feeling.